Dvadeset pet godina bilježenja prijevoda: hrvatsko i poljsko ogledalo / O dwudziestu pięciu latach przekładów literatury polskiej i chorwackiej — zwierciadła przekładu (tłum. Antonina Kurtok) - Gverić Katana, Petra (Przekłady Literatur Słowiańskich, 2016)
Twenty five years of translation: a cultural mirror of Croatian and Polish literature In this article, we have tried to draw an image of Croatian literature in Polish culture, as well as vice versa, in the last 25 years, based on bibliographies and articles on translations in PLS. It has been concluded that, due to translators’ choices of Croatian exile literature, works perceived in the source culture as non -canon, themes related to war, Yugonostalgia and authors whose work belong to the “borderline” of a few nations, Croatian literature in Poland exists as “Balkan” literature. On the other hand, choices of Polish literature in Croatia mainly concerns classic Polish authors. Both cases draw a wider picture of national imagery — a hetero -image – in the target culture. Key words: literature of exile, reception, Croatian translations, Polish translations, translation choices